TNF-α level and metabolic status in α-tocopheryl acetate supplemented high body condition periparturient crossbred cows during summer and winter - Chandra, Gulab; Aggarwal, Anjali; Singh, A K; Singh, Muneendra (The Indian Journal of Animal Sciences, 2012)
The study was conducted to investigate the effect of α-tocopheryl acetate supplementation on tumor necrosis factor- alpha (TNF- α) level and metabolic status in periparturient crossbred cows during summer and winter. High body condition periparturient crossbred cows (24) were selected, 12 each during summer and winter. For each season, 6 cows were kept as controls and 6 cows were supplemented with a-tocopherol acetate @ 1000 IU/ day/ cow, supplementation beginning 60 days prior to the expected date of calving. Blood samples were collected at –20, –10, –5, 0, 5, 10 and 20 days in relation to expected date of calving. Glucose value observed higher in winter treatment than other group cows. Non-esterified fatty acid concentration levels increased towards calving and were higher at day 5 postpartum in summer control in comparison to all other groups. Plasma TNF-α levels also increased toward calving but were higher at the day of calving, after that levels decreased towards day 20 postpartum in all the groups. The study indicated that metabolic statuses of high body condition crossbred cows were improved by supplementation of α-tocopherol acetate.